2010
DOI: 10.1017/s1751731110000911
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for optimizing nitrogen use by ruminants

Abstract: The efficiency of N utilization in ruminants is typically low (around 25%) and highly variable (10% to 40%) compared with the higher efficiency of other production animals. The low efficiency has implications for the production performance and environment. Many efforts have been devoted to improving the efficiency of N utilization in ruminants, and while major improvements in our understanding of N requirements and metabolism have been achieved, the overall efficiency remains low. In general, maximal efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
1
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(198 citation statements)
references
References 102 publications
9
165
1
15
Order By: Relevance
“…N balance was positive and similar between diets with the same N distribution between milk, faeces and urine. In addition, average N efficiency (N in milk/N intake) was similar between CON and LIN + NIT (30%) and close to the data given in the literature (25%, with a range between 15% and 40%, Calsamiglia et al, 2010). This result shows that dairy cows use nitrate in the same way as they use other N sources.…”
supporting
confidence: 87%
“…N balance was positive and similar between diets with the same N distribution between milk, faeces and urine. In addition, average N efficiency (N in milk/N intake) was similar between CON and LIN + NIT (30%) and close to the data given in the literature (25%, with a range between 15% and 40%, Calsamiglia et al, 2010). This result shows that dairy cows use nitrate in the same way as they use other N sources.…”
supporting
confidence: 87%
“…It has been estimated that hyper-ammonia producing bacteria have a lower substrate affinity (K m ) than the mixed ruminal bacteria, but the V max of ammonia production is ∼12.5-fold greater than the mixed ruminal bacteria of forage fed animals (Rychlik and Russell, 2000). Therefore, a higher RDP content in the diet could impact both SAD and the concentration of ruminal ammonia, demonstrating the influence of the diet in the activity of rumen microorganisms and nitrogen metabolism in the rumen (Bach et al, 2005;Calsamiglia et al, 2010). Nonetheless, the RDP supplementation did not alter (P > 0.05) the concentration of microbial protein among treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing dietary CP concentration in cattle fed silage-based rations has been related with small responses in BW gain and increased emissions of N and P (Huuskonen et al, 2014), feeding supplementary protein to cattle fed tropical forages can increase feed efficiency reduces excessive nitrogen losses to the environment (Agle et al, 2010;Calsamiglia et al, 2010) and increases overall animal performance . Detmann et al (2014) showed positive response to rumen degradable protein (RDP) supplementation on forage intake and nitrogen use efficiency with concomitant positive response in animal performance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, univariate meta-analysis showed reduced N output in faeces and urine and improved N-use efficiency in dairy cattle, from 0.25 to 0.30, upon a decrease in N intake from 600 to 300 g/day, respectively (Kebreab et al, 2010). The average N-utilization efficiency in dairy cattle is some 0.25 (range: 0.15 to 0.40; Calsamiglia et al, 2010). Major improvements in N efficiency at the animal level have been shown in practice through increased production levels and reduced dietary N contents (Figure 1).…”
Section: Diet Effects On Level Of N In Urinementioning
confidence: 99%